ULTRA-THIN SHEET STEEL AND METHOD FOR MANUFACTURING THE SAME - RYU, NAOTOSHI; TOSAKA, AKIO; OKUDA, KANEHARU; ARATANI, MASATOSHI; KUGUMINATO, HIDEO; ARATANI, MAKOTO; OKADA, SUSUMU (1998)
A steel slab is rough-rolled into a sheet bar and butt-joined onto a preceding sheet bar and a widthwise end portion of the sheet bar is heated by means of an edge heater and then subjected to a continuous finish rolling through pair-cross rolls rolling on at least 3 stands to provide a hot rolled steel strip having a width of not less than 950 mm, a thickness of 0.5-2 mm and a crown within +/-40 mu m, and the hot rolled steel strip is subjected to cold rolling, continuous annealing, temper rolling and, if necessary, plating treatment on the surface of the cold rolled steel strip, whereby there is obtained a steel sheet having an average thickness of not more than 0.20 mm and a width of not less than 950 mm, a thickness variation quantity in a widthwise direction is within +/- 4% of the average thickness in a region corresponding to not less than 95% of the width of the steel sheet as cold rolled and a hardness (HR30T) variation in the widthwise direction is within +/-3 of an average hardness.